PERANCANGAN SISTEM INFORMASI AKADEMIK PADA SMA DARUL FIKRI MUARO JAMBI BERBASIS WEB - Setya Pradana, Putra; Amroni, Amroni; Irawan, Beni (JOURNAL V-TECH (VISION TECHNOLOGY), 2021)
MTS Negeri 1 Muaro Jambi is one of the state schools located on Jl. Pelabuhan, Talang Duku, Kec. Taman Rajo,Kabupaten Muaro Jambi, Jambi. Academic information system that is applied is still not effective and efficient,because it has not been entirely managed in a computerized manner such as processing student data, teacher data,subject data, absenteeism, assignment data, semester scores, lesson schedules, report cards and report cards stillapply the manual system and cannot be accessed online, by processing data files in the form of documents.Applications used for data storage and processing at this time are Ms. Excel and Ms. Word, without a database.Therefore, this study aims to provide solutions to problems that occur by offering an academic information systemdesign using the PHP programming language and MySQL database where the author develops the system using thewaterfall method and uses a unified model language (UML) system approach using usecase diagrams, activitydiagrams, class diagrams and flowchart diagrams. The new system produces outputs that can manage data aboutprocessing academic data online.